Rate of Re-excision after Breast-conserving Surgery for Invasive Lobular Carcinoma. Issue 10 (October 2013) - Wanis, Morcos L.; Wong, Jennifer A.; Rodriguez, Samuel; Wong, Jasmine M.; Jabo, Brice; Ashok, Arjun; Lum, Sharon S. J.; Solomon, Naveenraj L.; Reeves, Mark E.; Garberoglio, Carlos A.; Senthil, Maheswari
Invasive lobular carcinoma (ILC) accounts for approximately 5 to 20 per cent of all breast cancers and is often multicentric. Despite pre- and intraoperative assessments to achieve negative margins, ILC is reported to be associated with higher rates of positive margin. This cross-sectional study examined patients with breast cancer treated at our institution from 2000 to 2010. The objective was to investigate the rate of re-excision resulting from positive or close margin (1 mm or less) in patients who underwent breast-conserving surgery (BCS) for ILC compared with invasive ductal carcinoma (IDC) and ductal carcinoma in situ (DCIS). Of the 836 patients treated, 416 patients underwent BCS. The rate of re-excision after BCS for ILC was 35.1 versus 17.7 per cent for IDC and 20.0 per cent for DCIS ( P = 0.04). Re-excisions were more often performed for positive margin in patients with ILC (11 of 37 [29.7%]) versus IDC (36 of 334 [10.8%]) and DCIS (five of 45 [11.1%];( P = 0.004). In this single-institution review, BCS for ILC had significantly higher rates of re-excision as a result of positive margins when compared with IDC and DCIS. Tumor size greater than 2 cm and lymph node involvement were identified as factors associated with positive surgical margin in ILC. The higher possibility of positive margins and the need for additional procedures should be discussed with patients undergoing BCS for ILC.